Вплив трансплантації ембріональних прогеніторних клітин на функцію нирок = Effect of transplantation embryonic progenitor cells on renal function - V. M. Sirman; R. N. Borys; O. P. Nykytenko; W. Zukow; A. I. Gozhenko (Kazimierz Wielki University, 2016)
Sirman V. M., Borys R. M., Nykytenko O. P., Zukow W., Gozhenko A. I. Вплив трансплантації ембріональних прогеніторних клітин на функцію нирок = Effect of transplantation embryonic progenitor cells on renal function. Journal of Education, Health and Sport. 2016;6(2):349-366. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56017 http://ojs.ukw.edu.pl/index.php/johs/article/view/3614   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016.   УДК: 616.61-008-089.843:615.361.013     В. М. Сірман, Р. М. Борис, О. П. Никитенко, В. Жуков, А. І. Гоженко   Український науково-дослідний інститут медицини транспорту МОЗ України, м. Одеса, Украина UMK w Toruniu Резюме Метою нашого дослідження було вивчення  впливу трансплантації ембріональних прогеніторних клітин на функцію нирок при експериментальному перитоніті та при ад'ювантному артриті Пірсона у щурів. У роботі використано 189 самців білих щурів з середньою масою тіла 0,193±0,018 кг. Дослідження проводили через 2, 4, 6 і 12 міс. після індукції ад'ювантного артриту Пірсона.  При експериментальному перитоніті, проведено 7 серій експериментів на 486 самцях білих щурів з масою тіла 0,17-0,30 кг. Встановлено, що при обох експериментальних моделях запалення трансплантація ембріональних прогеніторних клітин сприяє значному підвищенню діурезу за рахунок збільшення швидкості клубочкової фільтрації, що суттєво знижує вміст креатиніну у плазмі крові. Крім того, під впливом трансплантації ембріональних прогеніторних клітин спостерігається дворазове зниження втрат білка з кінцевою сечею, стандартизованих за об'ємом клубочкового фільтрату.   Ключові слова: гостре ураження нирок, ШКФ, трансплантація ембріональних прогеніторних клітин.     EFFECT OF TRANSPLANTATION EMBRYONIC PROGENITOR CELLS ON RENAL FUNCTION   V. M. Sirman, R. M. Borys, O. P. Nykytenko, W. Zukow, A. I. Gozhenko   Ukrainian Scientific Research Institute of Transport Medicine, Ministry of Health of Ukraine UMK w Toruniu Resume The aim of our study was to examine the influence of transplantation of embryonic progenitor cells in renal function in experimental peritonitis and in adjuvant arthritis in rats Pearson. The paper used 189 male albino rats with an average body weight of 0,193 ± 0,018 kg. The study was conducted at 2, 4, 6 and 12 months. After induction of adjuvant arthritis Pearson. In experimental peritonitis, held 7 series of experiments on 486 white male rats weighing 0,17-0,30 kg. Found that in both experimental models of inflammation transplantation of embryonic progenitor cells contributes to a significant increase in urine output by increasing glomerular filtration rate, which significantly reduces creatinine in blood plasma. In addition, under the influence of transplantation of embryonic progenitor cells there is a twofold decrease loss of protein from the final urine volume standardized glomerular filtrate.   Keywords: acute kidney damage, GFR, Transplantation of embryonic progenitor cells.